Modeling response of tree slenderness to climate, soil, diversity, and competition in natural secondary forests - Wang, Junjie; Wang, Youzhu; Tian, Dongyuan; Wang, Weifang; Jiang, Lichun (Forest ecology and management, 2023)
•Interactions of climate, soil, diversity, and competition notably affected tree slenderness.•Interactive effects of indicators were greatest in small-sized trees.•Effect direction of one indicator varied with the gradients of other indicators.•Negative effects of climate and soil on stability can be improved by adjusting density and diversity. The tree slenderness coefficient (TSC) serves as a simplified measure of tree stability, which is subject to the complex influences of climate, soil, diversity, and competition. Quantifying and exploiting the risks affecting the TSC facilitates the development of forest stability restoration measures. In the current climate change and multiple risk coexistence scenario, the interactions of risks are expected to have non-negligible effects on the TSC. However, past efforts have been limited to independent effects without interactive effects, which is detrimental to a proper understanding of ecology. For example, the inconsistent effect direction of the same indicator on TSC in past studies may be due to the neglect of the interactive effects of the indicators. Natural secondary forests are effective mitigation tools for climate change that urgently need to be managed appropriately to maximize their stability and provide a wide range of benefits. Therefore, we conducted the first comprehensive investigation of both independent and interactive effects of climate, soil, diversity, and competition on TSC, utilizing data from 13,874 trees of three principal tree species distributed in Chinese boreal natural secondary forests. Further, simulation examples were provided to present actionable management measures using the improved insight. The results showed that short-wave solar radiation (Srad), cation exchange capacity (CEC), Pielou evenness index (Pielou), and basal area (BA) exerted positive independent influences on TSC, while mean annual precipitation (MAP) did the opposite. The significant interaction terms were BA × Pielou, BA × Srad, Pielou × CEC, and Srad × CEC, all of which showed positive effects on TSC. In addition, the interactions produced non-negligible forces on the TSC, especially for small-sized trees, as the relative importance was quite large. Importantly, the effect directions of the indicators on the TSC were inconstant and changed with the gradients of other indicators due to the presence of interactions. Finally, the simulation results showed that tree stability in 97.1% of the plots was negatively affected by Srad or CEC, which could be transformed into positive effects by adjusting BA or Pielou above the critical points. This research offers a novel insight into the importance of interactions in credible TSC modeling and indicator analysis, which may hopefully serve as a beginning to guide forest management based on tree stability while faced with environmental change.